An Exploratory Study of College Students' Attitudes Toward Dietary Protein: Development of a Dietary Protein Assessment Survey Instrument (P16-047-19). (13th June 2019) - Ackerman, Parker; Warren, Cynthia; Wildman, Robert; Miketinas, Derek
Abstract: Objectives: The purpose of this exploratory study was to develop a survey to estimate college students' attitudes towards dietary protein. This analysis explored the dimensionality of the attitude constructs in the Dietary Protein Assessment Survey Instrument. Methods: The survey consisted of 64 questions, including 8 demographic questions, 24 knowledge questions, 14 attitude questions, and 18 behavior questions. The attitude questions included a 5-point Likert scale ranging from "strongly disagree" to "strongly agree" with a neutral midpoint. The dimensionality of the attitude constructs was explored by exploratory factor analysis (EFA) using principal axis factoring and a promax rotation. Internal consistency reliability was examined using Cronbach's alpha. Results: Two hundred twenty-five subjects (91.1% female) provided responses; mean age was 27.8 + 11.7y. After removing items that did not factor, the EFA retained three factors which explained 70.2% of the variance. Factor 1 consisted of 6 items, factor 2 and 3 consisted of 2 items each. Factor 1 included 6 items related to animal versus plant sources and their relationship with human and environmental health; factor 2 included 2 items pertaining to the healthfulness of organic protein sources; and factor 2 included 2 items describing the adequacy of the RDA for protein with respect to weight loss and adherence to a vegetarian diet. Factor 1 shared a moderate, positive relationship with factor 2 ( r  = 0.48) and a weak, inverse relationship with factor 3 ( r  = −0.33). Factor 2 shared a weak, inverse relationship with factor 3 ( r  = −0.30). The Kaiser-Meyer-Oklin test (0.817) and Bartlett's test of sphericity ( P  < 0.001) indicated that the data were appropriate for EFA. There was no evidence of multicollinearity (determinant = 0.01). Conclusions: Attitudes towards protein appear to be multi-dimensional and correlated. Further testing is needed to confirm the hypothesized 3-factor model and to estimate test-retest reliability of this survey. Funding Sources: Dymatize.